(untitled) (London Journal of Research In Humanities and Social Sciences, 2023)
In the current study, comments on the YouTube video series “Chinese festival food” were collected using an open-source web crawler. Sentiment analysis was conducted using the VADER sentiment analysis tool, and the topic distribution of sentiment tendencies was explored based on the LDA model. The study found that: (1) high frequency words and their collocations in the comments of Li Ziqi’s “Chinese festival food” video series indicated that viewers greatly appreciated the content. (2) The comments of Li Ziqi’s “Chinese festival food” video series conveyed a positive sentiment. (3) The positive sentiment of Li Ziqi’s “Chinese festival food” video series mainly focused on topics such as food, video, characters, life, and culture. These findings demonstrate that social media has become an emerging and powerful channel for cultural transmission and transcultural communication. This study aims to provide new research methods and ideas for the study of cultural transmission, and shed light on the transmission of culture across the world.